Pengapusan Hak Veto Dalam Rangka Reformasi Dewan Keamanan Perserikatan Bangsa-Bangsa - Afrilianti, Dewi; Ardianto, Budi; Pebrianto, Dony Yusra (Faculty of Law, Universitas Jambi, 2021)
This study aims to find out what is the reason the veto is considered irrelevant to the Security Council in realizing world security and peace in connection with the plan of veto power in the framework of reform of the United Nations Security Council because the use of veto rights by the five permanent member states of the Security Council, especially the United States has been used with no limits. The research method used is normative type with statutory, conceptual, and case approach. The results of this study show that the security council's veto power in practice has deviated from its original intent. The reform efforts of the United Nations Security Council have many obstacles but the main obstacles that greatly hinder the reform efforts are the arrogant, selfish, and willless nature of the permanent members of the United Nations Security Council who are veto holders to continue to maintain their hegemony and national interests. Keywords: United Nations; Right; Veto;